Controle Ótimo Aplicado em um Modelo de Câncer - Ramos, Eduardo [UNESP] (2015)
In the worked here presented we study the theory of Optimal Control. We also studied results in Theory of Di erential Equations focusing on Measure Theory, with the goal of proving the Pontryagin Mininum Principle, a necessary condition for optimality of a control. In turn, regularity and existence conditions for Optimal Linear Controls were also studied, since they are essential for determination of optimal controls. Finally, we used the theory of Optimal Control above mentioned for an analysis of a model of tumor with chemotherapy with the goal of minimizing the quantity of chemotherapy applied in the treatment